TMEM150A overexpression was associated with poor prognosis and cancer progression in glioma verified by comprehensive analysis and cell experiments - Hao-Qiang Xu; Dan Zhao; Shi-Hao Xu; Rui Mao; Wen-Qiong Yang; Qi Han (Scientific Reports)
Abstract Transmembrane (TMEM) proteins play a pivotal role in cancer progression, with TMEM150A specifically implicated in tumorigenesis. Despite its association with cancer, the precise role of TMEM150A in glioma remains underexplored. The expression of TMEM150A in glioma and its correlation with prognosis and the immune microenvironment were systematically analyzed. Prognostic models were developed using nomograms to establish the relationship between TMEM150A expression and patient survival. Bioinformatic analyses identified pathways and networks associated with TMEM150A co-expressed genes, while in vitro assays (CCK-8, migration, and invasion assays) examined the impact of TMEM150A inhibition on glioma cell proliferation and metastasis. TMEM150A was markedly overexpressed in glioma tissues and strongly associated with clinical features such as 1p/19q codeletion, age, IDH mutation status, histological subtype, WHO grade, and poor prognosis (P < 0.05). ROC analysis revealed high diagnostic accuracy, with area under the curve values of 0.962 and 0.896 for TCGA and XENA datasets, respectively, indicating the strong diagnostic potential of TMEM150A. Overexpression of TMEM150A was identified as a risk factor for poor prognosis. The constructed nomogram demonstrated that TMEM150A expression was predictive of survival, with time-dependent AUCs for 1, 3, and 5 years exceeding 0.75, confirming its prognostic relevance. TMEM150A co-expressed genes were linked to immune responses, necrotic cell death, antigen processing and presentation, cell differentiation, mast cell activation, endothelial cell migration, wound healing, and cell proliferation. Inhibition of TMEM150A expression suppressed U251 cell growth, migration, and invasion via epithelial-mesenchymal transition (EMT). Additionally, TMEM150A expression correlated with immune scores (r = 0.585), stromal scores (r = 0.498), ESTIMATE scores (r = 0.565), macrophage infiltration (r = 0.523), aDC (r = 0.473), and neutrophil presence (r = 0.453). Overexpression of TMEM150A serves as an independent prognostic marker in glioma and is intricately linked to the tumor’s immune microenvironment. Targeting TMEM150A could inhibit glioma progression through EMT modulation, presenting a potential novel therapeutic avenue.